2001
DOI: 10.1029/2000gl012765
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguration timescales of ionospheric convection

Abstract: Abstract. Changes in ionospheric flow patterns provide direct observations of how the magnetosphere-ionosphere system is coupled to the IMF. The nature and location of reconnection on the magnetopause is communicated to the ionosphere, which responds by reconfiguring global convection patterns. We investigate the dynamics of the changing global ionospheric convection patterns using a large twodimensional array of ground magnetometers. We have found that for sharp north to south transitions of the IMF, dayside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
62
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 11 publications
18
62
1
Order By: Relevance
“…However, in the real observation, nightside convection responds immediately to the changes in IMF, as does dayside convection (Kikuchi et al 1996;Ridley et al 1997Ridley et al , 1998Murr and Hughes 2001). In this model, the center of two-cell convection moves little associated with the development of convection.…”
Section: Reconstruction Of Convection After the Southward Turning Of Imfmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the real observation, nightside convection responds immediately to the changes in IMF, as does dayside convection (Kikuchi et al 1996;Ridley et al 1997Ridley et al , 1998Murr and Hughes 2001). In this model, the center of two-cell convection moves little associated with the development of convection.…”
Section: Reconstruction Of Convection After the Southward Turning Of Imfmentioning
confidence: 99%
“…This is widely accepted because, for a long time, the ingenuity ideas on the magnetospheric convection presented by Dungey (1961) led many people to believe them unconditionally. The well-known problem for which such interpretation results in an inconsistent understanding is the reconstruction problem of ionospheric convections after the southward turning of the IMF (Ridley et al 1997;Khan and Cowley 1999;Murr and Hughes 2001;Hashimoto et al 2002).…”
Section: Reconstruction Of Convection After the Southward Turning Of Imfmentioning
confidence: 99%
“…Radar and ground magnetometer observations demonstrated that elec-tric fields in the ionosphere show initial responses almost simultaneously in the entire ionosphere [Nishida, 1968;Ridley et al, 1998;Ruohoniemi and Greenwald, 1998;Murr and Hughes, 2001]. Observations of ground magnetic fields indicate that convection electric fields in the ionosphere propagate toward the dip equator almost instantaneously (within 25 s) [Kikuchi et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…[34] A typical example that shows an observational evidence for the compound nature of convection from the ionospheric observation is the controversy about the reconfiguration time scale of ionospheric convection [Lockwood and Cowley, 1999;Murr and Hughes, 2001]. It is a natural consequence from the simple Dungey's convection to believe that the convection on the nightside ionosphere cannot be driven before the tail magnetosphere knows the change of the convection.…”
Section: Observational Confirmations From Ionospheric Convectionmentioning
confidence: 99%